Memory Reclamation Methods for Lock-Free Hash Tries - Moreno, Pedro; Areias, Miguel; Rocha, Ricardo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD); 2019: Anais do XXXI International Symposium on Computer Architecture and High Performance Computing, 2019)
Hash tries are a trie-based data structure with nearly ideal characteristics for the implementation of hash maps. Starting from a particular lock-free hash map data structure, named Lock-Free Hash Tries (LFHT), we focus on solving the problem of memory reclamation without losing the lock-freedom property. We propose an approach that explores the characteristics of the LFHT structure in order to achieve efficient memory reclamation with low and well-defined memory bounds. Experimental results show that our approach obtains better results when compared with other state-of-the-art memory reclamation methods and provides a competitive and scalable hash map implementation, if compared to lock-based implementations.